HOMOEOPATHIC MANAGEMENT OF TARGETED HAEMARTHROSES IN INHIBITOR POSITIVE HAEMOPHILIAC: A CASE REPORT - Kumat, Omkar; Kundu, Tapas; Mirza, Gulfisha; Kundu, Rita (International Journal of Research -GRANTHAALAYAH, 2024)
Haemarthroses is common presentation in haemophilia patient. Due to recurrent use of clotting factor concentrates for treatment and prophylaxis, of which about 20 % of patients produce antibodies to factor VIII and factor IX. This results in development of inhibitors in such patients which complicates the case even more. Homoeopathy the alternative form of treatment can be used in such case. This case report presents the management of haemarthroses in a haemophilia inhibitor. Well selected homoeopathic similimum helped in reversing the haemophilic arthropathy in left knee joint of the patient and even controlled the recurrence of the haemarthroses in target joint. The result was assessed using Hemophilia joint health assessment scale (HJHS). The result of before and after treatment was extremely significant with a p value of 0.0009 The individual curative response of the case was assessed using Modified naranjo criteria for homoeopathic case reporting, casual attribution (MONARCH).